Optimizing open-pit block scheduling with exposed ore reserve - Saavedra-Rosas, Jose; Jélvez, E.; Amaya, J.; Morales, N. (Southern African Institute of Mining and Metallurgy, 2016)
© 2016 The Southern African Institute of Mining and Metallurgy.A crucial problem in the open pit mining industry is to determine the optimal block scheduling, defining how the orebody will be sequenced for exploitation. An orebody is often comprised of several thousand or million blocks and the scheduling models for this structure are very complex, giving rise to very large combinatorial linear problems. Operational mine plans are usually produced on a yearly basis and further scheduling is attempted to provide monthly, weekly, and daily schedules. A portion of the ore reserve is said to be exposed if it is readily available for extraction at the start of the period. In this paper, an integer programming (IP) model is presented to generate pit designs under exposed ore reserve requirements, as an extension of the classical optimization models for mine planning. For this purpose, we introduce a set of new binary variables, representing which blocks can be declared as exposed ore reserve, in addition to the extraction and processing decisions. The model has been coded and tested in a set of standard instances, showing very encouraging results in the generation of operational block schedules.